Material Extrusion 3D Printing (ME3DP) Process Simulations of Polymeric Porous Scaffolds for Bone Tissue Engineering - Ramsha Imran (12431698) (2023)
Bone tissue engineering (BTE) is an active area of research for bone defect treatment. Some polymeric materials have recently gained adequate attention as potential materials for BTE applications, as they are biocompatible, biodegradable, inexpensive, lightweight, easy to process, and recyclable. Polyetherimide (PEI), acrylonitrile butadiene styrene (ABS), and polyamide-12 (PA12) are potential biocompatible materials for biomedical applications due to their excellent physical, chemical, and mechanical properties. The current study presents preliminary findings on the process simulations for 3D-printed polymeric porous scaffolds for a material extrusion 3D printing (ME3DP) process to observe the manufacturing constraints and scaffold quality with respect to designed structures (porous scaffolds). Different unit cell designs (ventils, grid, and octet) for porous scaffolds, virtually fabricated using three polymeric materials (PEI, ABS, and PA12), were investigated for process-induced defections and residual stresses. The numerical simulation results concluded that higher dimensional accuracy and control were achieved for grid unit cell scaffolds manufactured using PEI material; however, minimum residual stresses were achieved for grid unit cell scaffolds fabricated using PA12 material. Future studies will include the experimental validation of numerical simulation results and the biomechanical performance of 3D-printed polymeric scaffolds. Other Information Published in: Materials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ma16062475